2014
DOI: 10.1161/hypertensionaha.113.01360
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antihypertensive Treatment Fails to Improve E/e′ Despite Regression of Left Ventricular Mass

Abstract: Abstract-Antihypertensive treatment can improve tissue Doppler indices of left ventricular diastolic function in the shortterm, but little is known about the longer-term effect of different antihypertensive treatments on progression of left ventricular diastolic function and left ventricular hypertrophy. We hypothesized that long-term treatment of hypertension will lead to improvements in left ventricular hypertrophy and diastolic function. We collected detailed cardiovascular phenotypic data on 1006 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
(41 reference statements)
2
22
0
4
Order By: Relevance
“…69, 81, 106, 107 Interestingly, the magnitude of reduction in LV mass was found to correlate only modestly with the extent of BP decline 81 . Muiesan et al 69 also observed an impact of antihypertensive treatment on LV geometry, with a normalization of LV geometry occurring in 9% of the 436 subjects and associated with a better prognosis.…”
Section: Impact Of Antihipertensive Treatment On Cardiac Structure Anmentioning
confidence: 97%
See 1 more Smart Citation
“…69, 81, 106, 107 Interestingly, the magnitude of reduction in LV mass was found to correlate only modestly with the extent of BP decline 81 . Muiesan et al 69 also observed an impact of antihypertensive treatment on LV geometry, with a normalization of LV geometry occurring in 9% of the 436 subjects and associated with a better prognosis.…”
Section: Impact Of Antihipertensive Treatment On Cardiac Structure Anmentioning
confidence: 97%
“…However, two randomized clinical echocardiography sub-studies with larger sample sizes and longer duration of follow-up demonstrated no impact of antihypertensive therapy on diastolic function, despite adequate blood pressure control and significant regression of LV mass 81, 106 . This dissociation between structural and functional improvement may be related to the multifactorial pathogenesis of diastolic dysfunction.…”
Section: Impact Of Antihipertensive Treatment On Cardiac Structure Anmentioning
confidence: 98%
“…33 In a post hoc analysis of the ASCOT trial, a 1 mm Hg increase in SBP was associated with 2% higher baseline NT-proBNP (N-terminal pro-B-type natriuretic peptide), and this predicted adverse cardiovascular events with a 22% net reclassification improvement of cardiovascular risk. 34 Indeed, biomarkers, such as natriuretic peptides, allow identification of conditions related to LV volume overload, including those related to hypertension (eg, LV hypertrophy, diastolic dysfunction, and heart failure with preserved ejection fraction).…”
Section: Effect Of Antihypertensive Treatment On Diastolic Dysfunctiomentioning
confidence: 99%
“…Результати нашого дослідження щодо змін по-казника Е/Е' відрізняються від даних піддосліджен-ня дослідження ASCOT [8]. Показано, що на двох етапах спостереження на фоні терапії і амлодипіном (+ периндоприл), і атенололом (+ тіазид) відбува-лося майже однакове зменшення індексу ММЛШ (Р = НД).…”
Section: клінічні дослідження / Clinicial Researchesunclassified